Detection and diagnosis of periodontal conditions amenable to prevention. Issue 1 (December 2015) - Preshaw, Philip
Abstract Gingivitis and chronic periodontitis are highly prevalent chronic inflammatory diseases. Gingivitis affects the majority of people, and advanced periodontitis is estimated to affect 5-15% of adults. The detection and diagnosis of these common diseases is a fundamentally important component of oral health care. All patients should undergo periodontal assessment as part of routine oral examination. Periodontal screening using methods such as the Basic Periodontal Examination/Community Periodontal Index or Periodontal Screening Record should be performed for all new patients, and also on a regular basis as part of ongoing oral health care. If periodontitis is identified, full periodontal assessment is required, involving recording of full mouth probing and bleeding data, together with assessment of other relevant parameters such as plaque levels, furcation involvement, recession and tooth mobility. Radiographic assessment of alveolar bone levels is driven by the clinical situation, and is required to assess bone destruction in patients with periodontitis. Risk assessment (such as assessing diabetes status and smoking) and risk management (such as promoting smoking cessation) should form a central component of periodontal therapy. This article provides guidance to the oral health care team regarding methods and frequencies of appropriate clinical and radiographic examinations to assess periodontal status, to enable appropriate detection and diagnosis of periodontal conditions.